Development of an Integrated Islamic Religious Education Curriculum at Junior High School Integrated Islamic in Deli Serdang Regency - Muhammad Syafi’i; Wahyudin Nur Nasution; Neliwati Neliwati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the development of an integrated Islamic Religious Education (IRE) curriculum across Islamic Junior High Schools, each of which employs distinct curriculum design models to strengthen the internalization of Islamic values in students’ learning experiences. Methodology: Using a descriptive qualitative approach, data were gathered from principals, vice principals for curriculum, and IRE teachers through in-depth interviews, observation, and documentation. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, with validity ensured through triangulation and confirmability. Main Findings: The findings reveal three unique patterns of curriculum development: (1) Islamic Junior High School Al-Hijrah adopts Ralph Tyler’s curriculum model and applies the Integrated Subject Model, creating a cohesive fusion of Islamic content across disciplines; (2) Islamic Junior High School Nurul Fadhilah employs Taba’s Inverted Model and applies the Connected Model, strengthening inter-topic linkages within IRE learning to support conceptual coherence; and (3) Islamic Junior High School Nurul Ilmi utilizes the Rogers Interpersonal Relations Model and similarly adopts the Connected Model, emphasizing relational, student-centered integration of Islamic teachings. Novelty/Originality of this study: The novelty of this research lies in its comparative analysis of multiple curriculum development models within Islamic secondary education—an area rarely examined simultaneously. By mapping how different philosophical orientations and integration strategies shape IRE implementation, this study offers a multidimensional framework for schools to design contextually responsive, value-integrated curricula that enhance religious literacy, character formation, and holistic student development.